Setting-up of the Database on the Nucleotide Sequences of the Genomes of the Strains of Bacterial and Viral Infections Agents of the I–II Pathogenicity Groups - Yu. I. Yashechkin; E. V. Naydenova; T. V. Bugorkova; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2013)
Set-up is database containing characteristics of variable tandem repeats, oligo-nucleotide primers and probes of the genomes of the strains bacterial and viral infections agents of the I-II pathogenicity groups. It allows for accumulation of information on genome regions. Using the incorporated VBA one can rapidly analyze the data and carry out substantiated calculation of gene-diagnostic preparations based on various PCR frameworks.